Synthesis, Characterization and Antimicrobial Activities of mixed Ligand Metals Complexes with Trimethoprim and Potassium Thiocyanate - Olagboye, Sulaiman Adeoye (European Journal of Applied Sciences, 2022)
A new series of Mn (II) and Ni (II) mixed ligands-metal complexes derived from trimethoprim (TMP) and thiocyanate (TC) have been synthesized in aqueous medium and characterized by spectroscopic studies using IR. The coordination of the two ligands towards central metal ions has been proposed in the light of elemental analysis using barium chloride gravimetric method, various colours of metal complexes were obtained ranging from green to light green and found to be soluble in ethanol, butanol, and insoluble in n-hexane, propan-2-ol, and benzene. The following physical parameters were also observed; solubility, melting point and conductivity. The results of the physical and spectroscopic data confirmed that the ligands are chelating agents. The results of spectroscopic studies revealed that TMP acts as a mono-dentate ligand coordinating through the nitrogen of the pyrimidine group and coordination through the nitrogen of the amine group, while in the TC coordination occurred through the sulphur and nitrogen groups because thiocyanate shares its negative charge approximately equally between sulfur and nitrogen. As a consequence, thiocyanate can act as a nucleophile at either sulfur or nitrogen, it is an ambidentate ligand. Antimicrobial activity of the mixed ligands metal complexes and the free ligands were carried out against the bacterial Escherichia coli, Staphylococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa, Bacillius subtilis and the fungi; Sclerotinia trifoliorium, Fusarium oxyporium, Stemania paradoxa, Brotrytis cinerea. The mixed ligands metal complexes showed higher activities when compared to the free ligands of TMP but were less active than the free TC ligand. The complexes of Mn (II) showed the highest antimicrobial activity while the Ni (II) complex showed the least activity against the bacterial and fungi organisms. Structure activity relationship showed that Ni (II) complexes containing sulphate ions are more active, while for Mn (II) complexes containing thiocyanate ions showed more enhanced activity than those containing sulphate ions.